Discovery of novel anti-parkinsonian effect of schisantherin A in in vitro and in vivo. (23rd April 2015) - Sa, Fei; Zhang, Lun Qing; Chong, Cheong Meng; Guo, Bao Jian; Li, Sai; Zhang, Zai Jun; Zheng, Ying; Hoi, Pui Man; Lee, Simon Ming Yuen
Highlights: The neuroprotection of five dibenzocyclooctadiene lignans were investigated. Schisantherin A protects against MPP + and MPTP in vitro and in vivo. Benzoyloxy substituent group is functionally important for neuroprotection. The mechanism relies on increasing CREB-mediated Bcl-2 expression. The mechanism relies on activating PI3K/Akt survival signaling. Abstract: Dibenzocyclooctadiene lignans represent a unique group of natural chemical structures, are considered as protectants against neuronal cell death and cognitive impairment in neurological disorders. Among the family of dibenzocyclooctadiene lignan analogs from the fruit of Schisandra chinensis (Turcz.) Baill, neuroprotective potential of schisantherin A (StA) has not yet been characterized. In this study, 1-methyl-4-phenylpyridinium ion (MPP + )-incubated SH-SY5Y cells and 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP)-treated mice were used to study the neuroprotection of StA. Pretreatment with StA significantly inhibited MPP + -induced cytotoxicity in SH-SY5Y cells. Moreover, StA conferred significant protection against MPTP-induced loss of TH-positive dopaminergic neurons in a Parkinson's disease (PD) mice model. Structure activity relationship analysis suggested that methylenedioxy, benzoyloxy and methoxyl groups, in the dibenzocyclooctadiene lignan of StA, were probably functionally important to its neuroprotective activity. In addition, Western blotting analysis demonstrated that StA exhibited neuroprotection against MPP + through the regulation of two distinct pathways including increasing CREB-mediated Bcl-2 expression and activating PI3K/Akt survival signaling suggesting that StA might be a promising neuroprotective agent for the prevention of PD.